A New Midcourse Guidance Design for Near Space Target Interceptor - Wu, Yanrui; Xiao, Mingqing; Zhang, Danxu; Peng, Weishi; Xu, Yang; Dong, Xinyu (IEEE access, 2020)
This study proposes a new midcourse guidance method, combining the trajectory optimization approach and the optimal sliding mode method, to decrease the larger relative velocity between the near space target and the interceptor. Firstly, the midcourse trajectory optimization model is established. Then, the trajectory optimization guidance law based on a sampling scheme is proposed to decrease the larger relative velocity and satisfy multiple constraints at the end time of the midcourse guidance phase. Thirdly, the optimal sliding mode guidance law is introduced to deal with the target maneuverability. Finally, numerical simulations were performed to verify the performance of the midcourse guidance law.